An Experimental Study to Explore the Effectiveness of a 3D Maritime Serious Game Prototype: Maritime Leaders at Sea - Gurbuz, Suleyman Cihan; Celik, Metin (Transactions on Maritime Science, 2024)
This paper conducts a comprehensive experimental study designed to investigate the effectiveness of a maritime serious game called Maritime Leaders at Sea (ML@S). The 3D cutting-edge prototype targets to enhance leadership and teamwork skills of undergraduate maritime students via engaging them in immersive gameplay scenarios reflective of real-world challenges at sea. Competing the ML@S sessions, the number of 76 students were included in the feedback assessment survey to assess their perceptions and attitudes on the simulated environment. The feedback is also linked to the learning analytics perspective to involve time and scoring data of players through different levels at operational scenarios. Preliminary analyses reveal promising results, suggesting a positive correlation between participation in ML@S, feedbacks after sessions, and improvements in leadership and teamwork as key competencies. It is anticipated that this study will make significant contributions towards game developers, technology start-ups, educational institutions, and global shipping companies. The implications of the study offer valuable insights for the development of future serious games aimed at enhancing essential skills of maritime human resources in dynamic and high-stakes environments.